Pharmacist-Physician Collaboration at a Family Medicine Residency Program: A Focus Group Study - Keri Hager; Courntey Murphy; Don Uden; Brian Sick (University of Minnesota Libraries Publishing, 2018)
Background: In response to transforming healthcare and pursuit of the Triple Aim, many health systems have added team members to expand the capabilities and effectiveness of the team to facilitate these aims. The objective of this study was to explore knowledge and perceptions of pharmacist-physician collaboration among family medicine residents (FMR), family medicine faculty (FMF), and pharmacist faculty and residents in a practice where clinical pharmacy services were relatively new. Understanding the nuances of pharmacist-physician interactions will provide insight into how to improve FMR education to prepare learners for patient-centered, team-based practice. Methods: An exploratory descriptive qualitative study design was used to articulate perceptions of professional roles and team-based care in an interprofessional family medicine community-based clinical practice. Five, 60-minute focus groups were conducted in a clinical training setting that focuses on preparing family medicine physicians for collaborative rural primary care practice. Results: Twenty-one FMRs, eight FMF, and six clinical pharmacists participated. Three themes emerged from the focus groups and were consistent across the groups: 1) roles of pharmacists recognized by physicians in different settings, 2) benefits to collaboration, and 3) keys to successful pharmacist-physician collaboration which include a) developing the relationship, b) optimizing communication, c) creating beneficial clinical workflow, d) clarifying roles and responsibilities, and e) increasing opportunities for meaningful interactions. Conclusion: This study demonstrated that by co-locating physicians and pharmacists in the same environment, and providing a basic structure for collaboration, a collaborative working relationship can be initiated. Practices looking to have more effective collaborative working relationships should strive to increase the frequency of interactions of the professions, help the physicians understand the abilities of pharmacists, and help the pharmacists articulate to the physicians the value of what they provide to patients. The five keys identified in this study are building blocks to advance a successful collaborative working relationship that positively benefits patient care and achieves the Quadruple Aim. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties Treatment of Human Subjects: IRB exemption granted   Type: Original Research